EFEKTIFITAS PELATIHAN PENCEGAHAN GIZI BURUK BALITA PADA PEER EDUCATOR UNTUK MENINGKATAN PENGETAHUAN KELOMPOK DASAWISMA DI PUSKESMAS BATURRADEN I. - Arif Kurniawan; Elviera Gamelia (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
ABSTRACTResult of monitoring from Baturaden I Public Health Centers known that malnutrition and poor nutrition by 49 children ( 2.89% ). The results of this monitoring have not been able to portray the true condition of the status of children under five malnutrition in the community. One of the factors that influence malnutrition status is of knowledge about malnutrition . Efforts to increase community knowledge about malnutrition can be done with various models of health promotion. This study aims to determine the effectiveness of training peer educators malnutrition in dasa wisma group house at Baturaden I public health centers, Distric of Banyumas to increasing knowledge of prevention of malnutrition. This type of research was a quasi experimental study with one group pre -test and post-test design . The samples were in a group of housewives in the dasa wisma group in Baturraden I Public Health Centers many as 14 people. Analysis of the data used was a paired t – test. The variables measured were knowledge about peer education techniques, and knowledge about prevention of malnutrition. The result showed that the training was done by using the method of lecture, discussion and practice of malnutrition health promotion could increased knowledge about malnutrition prevention before training and after training. Training also effectively increased the knowledge about the peeer education techniques. Advice gived was increased efforts to combat malnutrition with more active health promotion about malnutrition through peer educator in the community. Keyword : Peer Educator, Malnutrition, Dasa Wisma Group Kesmasindo, Volume 7( 2), Januari 2015, Hal. 82-87